Lutetium-Specific Prostatic Membrane Antigen (LuPSMA) Treatment for Metastatic Castration-Resistant Prostate Cancer - Paixão, Sanna Verena Moreira; Silva, Carlos Danilo Cardoso Matos (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2024)
Introduction: Cancer is one of the leading causes of death globally, with the majority of cases occurring in low-income countries. There are more than a hundred types, divided into sarcomas and carcinomas. Prostate cancer is the most common cancer among men and is usually asymptomatic. Treatment depends on the stage of the disease and may include surgery, hormone therapy, and radiation therapy. In advanced stages, new treatments such as the radiopharmaceutical LuPSMA are investigated to improve patients' quality of life. Material and Methods: An exploratory-descriptive literature review was conducted using qualitative methods. Data collection spanned 2019–2024, sourcing relevant studies from LILACS, SciELO, and PubMed. Search terms included